The value of state education to consumers in the UK - Andreou, Sofia N.; Pashardes, Panos; Pashourtidou, Nicoletta (My University, 2018)
This paper considers the value of state schooling, as perceived by consumers, taking into account that many households supplement the minimum education provided free of charge with out-of-pocket payments through acquiring accommodation in the catchment area of a high-quality state school. It suggests ways to circumvent difficulties in modelling household behaviour arising from joint housing-education consumption in the context of a two-stage demand system, where the proposed money metric of state schooling can be estimated from data readily available in household expenditure surveys. The empirical analysis, based on UK data, estimates this money metric as the amount households with school-age children would be willing to accept in order to opt out of the state education system. The efficiency and distributional implications of the empirical findings are discussed.
Keywords: Consumer demand analysis; UK data; Valuation of state education